Disaster risk management of land and water-related natural hazards for Africa’s central highlands: Rwanda, Burundi, and the Democratic Republic of Congo - a review report - Lundh, A.; Barron, J.; Cofie, Olufunke O.; Tilahun, Seifu A. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
As a consequence of climate change, changes in land use, and land management—especially in densely populated areas—numerous natural disasters, such as floods, storms, heatwaves, landslides, and droughts, are becoming increasingly frequent, with severe impacts on living conditions. This is the case for Rwanda, Burundi, and the Democratic Republic of Congo (DRC). At the same time, intense farming practices (particularly on sloped land), deforestation activities, mining extraction operations, challenges in agriculture water management, and soil erosion all contribute to increased land vulnerability. The purpose of this study was to review how the risks of natural disasters related to flooding, landslides, and soil erosion are assessed, measured, managed, and mitigated in the central highlands of Africa, specifically in Rwanda, Burundi, and the DRC. In this process, the risks and the current status of disaster risk management, early warning systems, soil and land conservation practices, and risk mapping were investigated for the three countries.